KEMAMPUAN KEPEMILIKAN INSTITUSIONAL MEMODERASI PENGARUH DIVERSITAS GENDER, KEBANGSAAN, PENGALAMAN DEWAN PADA LUAS INTELLECTUAL CAPITAL DISCLOSURE - Vedanti Pratiwi, IA Ika; Badera, I Dewa Nyoman; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This research aims to obtain empirical evidence about the effect of gender diversity, nationality, experience on the wideness of IC Disclosure with institutional ownership as moderating variable. The sample of this research amounted to 78 companies from 440 non financial companies with intensive intellectual capital that are registered at BEI during period year of 2012-2015. Data analysis technique used in this research is multiple regression analysis and absolute difference value test. The result of this research show that gender diversity has negative impact on the wideness of IC Disclosure, nationality diversity has positive impact on the wideness of IC Disclosure, experience diversity has not impact on the wideness of IC Disclosure, the institutional ownership is able to moderate the effect of gender and nationality diversity on the wideness of IC Disclosure, the institutional ownership is not able to moderate the effect of experience diversity on the wideness of IC Disclosure.